Edge segmentation of Malay sign language images / Ahmad Zaki Bahrudin - Bahrudin, Ahmad Zaki (2017)
Edge based segmentation are the technique that have in image processing. In this project, three method form edge based segmentation technique which Canny segmentation method, Sobel segmentation method and Roberts segmentation method are choose. After use each three method and find the sum of value pixels, the value have pass to equation that calculate to find the best method with higher accuracy between that three method. The result each calculation have collect and save in excel to make comparison in percentage the best method have choose. As hope this system can help for future of any image processing technique might be relate with this system or can improvise with any brilliant idea.